INCORPORATION OF FATTY ACIDS IN FRESHWATER FISH: IMPLICATIONS FOR HUMAN NUTRITION - Oliveira, Diana Carla Fernandes; Miranda, Ana Luiza de Souza; Gomes, Maria Emília de Sousa; Borges, Rafael Antônio; Galuppo, Matheus Ribeiro; Vieira e Rosa, Priscila; Rosa, Renan Paulino; de Freitas, Rilke Tadeu Fonseca (Seven Editora, 2026)
Fish consumption has increased globally due to its recognized nutritional benefits and lower environmental impact compared to other sources of animal protein. In this context, aquaculture plays a central role in the supply of healthy foods, with Nile tilapia (Oreochromis niloticus) being one of the most relevant species worldwide and, especially, in Brazil. Fish stands out as a source of high-quality proteins, vitamins, minerals, and, mainly, polyunsaturated fatty acids of the omega-3 series, such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), associated with the prevention of cardiovascular, metabolic, and inflammatory diseases. This work aimed to analyze, through a literature review, the main aspects related to fish consumption, the benefits of omega-3 to human health, and the nutritional and genetic strategies for incorporating these fatty acids in tilapia. This review was conducted using the Web of Science, Scopus, and PubMed databases, encompassing studies in both Portuguese and English. The results demonstrate that, although the fatty acid composition of the fillet is strongly influenced by diet, genetic and metabolic factors play a determining role in the elongation and desaturation capacity of lipid precursors in tilapia. Evidence indicates that the species exhibits high efficiency in the biosynthesis of long-chain polyunsaturated fatty acids, and it is possible to enhance this process through nutritional management and genetic improvement. The application of nutrigenomic approaches and the use of genomic tools emerge as promising strategies for selecting strains with a more favorable lipid profile, contributing to the production of fish with greater nutritional value and benefits to human health.DOI: https://doi.org/10.56238/sevened2026.001-022